If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2) + -1y = 9 Multiply 3 * 2 6 + -1y = 9 Solving 6 + -1y = 9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1y = 9 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = 9 + -6 -1y = 9 + -6 Combine like terms: 9 + -6 = 3 -1y = 3 Divide each side by '-1'. y = -3 Simplifying y = -3
| 6b-6b+32=16 | | 2b+3c=12 | | -9+4x=6x+-13 | | 8-10y=-8y | | b-5+8b=33 | | 226.8=21.7y | | 8m(m-3)=56 | | -80-11x=5x+144 | | 216x+36=15+12x | | 3(r-3)+7r=54 | | y=8-6 | | y+g=12 | | 20y+3y= | | 216=36x+15+12x | | 24=w+8 | | 5x-11+5x=21 | | 5+4w=-8 | | 216+36x=15+12x | | 16y+11y= | | 5n^2+19n-69=-2 | | 24=w+6 | | 3y+1=21 | | -8x-163=101+3x | | -7.2=80x | | 17x=26 | | 8x-13x=26-34 | | 3m-[m+1]=6m+1 | | 42.34=9g+3.82 | | 6x-9=110-11x | | 7x+1=2x-4 | | 5x+2(3x+8)+17=4x+21 | | 5-3(x-7)=2(2-x) |